(untitled) (Nigerian Journal of Physiological Sciences, 2022)
The contribution of prefrontal-hippocampal interactions to brain function of people infected with HIV may be aggravated by toxicities due to long-term use of antiretroviral agents. This study was designed to investigate the curative potential of Epigallotatechin gallate (EGCG) in the treatment of neurodegenerative disorders as a possible consequence of antiretroviral toxicity. Twenty-four adult male Wistar rats, weighing 80 100g, were divided into four groups and treated as follows: control A (distilled water), B (HAART), C (EGCG 2.5mg/kg), D (EGCG 2.5mg/kg) + HAART) Brain histology, immunohistochemistry, and oxidative stress markers such as superoxide dismutase (SOD), glutathione (GSH),catalase (CAT) and malondialdehyde (MDA) were examined. The use of highly active antiretroviral therapy (HAART) showed extensive architectural deformation with pyknotic neuronal cells and obliterated neurons in the hippocampus and prefrontal cortex. Expression of inflammasome cells was also evident in this group. MDA levels increased significantly with a significant reduction in the levels of GSH, as well as antioxidant enzyme (SOD and CAT) activities compared to other treatment groups. Treatment with EGCG resulted in partial neuronal restoration of histopathological alterations, and modulation of NLRP3 inflammasome in the hippocampus and prefrontal cortex. EGCG also showed significant improvements in terms of increased antioxidant levels of SOD, GSH, CAT and a reduced MDA level and well-preserved brain architecture. Epigallocatechin gallate improves brain morphology and function with a reversal of HAART-induced alterations.